Relación entre malaria, desnutrición, inseguridad alimentaria y condiciones socioeconómicas, en niños de Turbo, Colombia (2009)
ABSTRACT: Malaria, malnutrition and household food insecurity are public health problems in Colombia that should be studied all an integrated way Objective: to study the association between malaria nutritional status, household food insecurity and socio-economic factors. Materials and methods: cross sectional study was carried out in a place called “El Tres”, Turbo-Colombia. Children 2-14 year old were divided in two groups: one group with malaria (76) and the other one without malaria (147). Nutritional status, food accessibility and socio-economic factors were analyzed. Results: prevalence of chronic malnutrition in children with malaria versus children with no malaria were: 39,5% and 25,2%, food insecurity was 94,7% and 92,5%, and mother’s scholar level was 3±3 y 4±3 (p=0,041), respectively. The risk to have malaria is increased in chronic malnutrition (OR:1,94;IC95%1,07-3,50) and by poor housing conditions as bad roof quality (OR:5,95;IC95%2,28-15,55), bad floor quality (OR:2,05;IC95%1,06-3,82) and not have electricity (OR:3,85;IC95%2,10-6,90). Conclusion: food insecurity was common in studied subjects, socio-economic conditions were low and the prevalence of chronic malnutrition was high. All these issues were strong associated with malaria. This is the first study carried out in Colombia that explores the association of malaria with child malnutrition and household food insecurity. Key words: malnutrition, food security, poverty, household food insecurity, socio-economic factors, children.